Changes in liver stiffness measurements following hepatitis C sustained virologic response among Alaska Native adults treated with sofosbuvir-based direct acting anti-viral therapy - Janet M. Johnston; Lisa Townshend-Bulson; Brian McMahon; Dana Bruden; Chriss Homan; Kena Desai; Wileina Rhodes; Youssef Barbour (International Journal of Circumpolar Health)
Direct-acting antiviral (DAA) hepatitis C treatment can reduce fibrosis and prevent cirrhosis and its sequelae. This study aims to evaluate changes in fibrosis and lab measurements from pre-treatment to post-treatment and over time following the end-of-treatment among Alaska Native and American Indian (AN/AI) peoples treated with sofosbuvir-based DAAs between 2014 and 2023. Study participants were predominantly male (53.9%) with a mean age of 54.4 years at start of treatment. Among the 290 (61.3%) participants with at least one pre- and one post-treatment Liver Stiffness Measurement (LSM), post-treatment LSM was significantly lower than pre-treatment LSM (p < 0.001). Median post-treatment LSM increased with increasing pre-treatment fibrosis stage (p < 0.001). Median values for ALT, AST, AFP, FIB-4 and APRI decreased significantly between pre- and post-treatment visits (p ≤ 0.002), while platelets remained stable (p = 0.827). The majority of AN/AI adults successfully treated with sofosbuvir-based DAAs experienced a reduction in LSM, with LSM subsequently remaining stable up to 4 years following end-of-treatment. Liver function and blood-based estimates of fibrosis also improved. The most important predictor of LSM improvement was pre-treatment fibrosis stage.